Dynamics Study of a Triangular Connecting Rod Toggle Press Mechanism with Considering the Kinematic Pair Clearance - Zhongshuang Wang; Jiuzheng Yin (Jixie chuandong)
For the dynamics modeling， simulation and analysis of a triangular connecting rod toggle press mechanism with considering the kinematic pair clearance， the corresponding vector bond graph procedure is proposed. Based on the kinematic pair clearance model of massless-link/spring damper， the vector bond graph model of a triangular connecting rod toggle press mechanism with kinematic pair clearance is built. By the corresponding method， all the energy storage elements of the mechanism vector bond graph possessed integral causality. Based on these， the computer modeling and dynamics simulation of a triangular connecting rod toggle press mechanism with kinematic pair clearance is realized by Matlab， the influences of kinematic pair clearance on the press mechanism kinematics and dynamics performance are analyzed， and the reliability and validity of the procedure proposed are illustrated.